Elective Open Groin Hernia Mesh Repair in All Risk Patients - Do We Need Antibiotic Prophylaxis? - Hussain, Muhammad Irshad; Inamullah, Inamullah; Hussain, Irshad; Shahzad, Khurram; Amir, Zainab; Musa, Suha Hassan Ali Abu; Saleem, Nitasha; Ali, Syed Muhammad (International Journal of Innovative Research in Medical Science, 2024)
Background: Open groin hernia repair with a prosthetic mesh is a very common surgical procedure performed worldwide. Although this is a clean surgery, the risk of surgical site infection (SSI) is always there when prosthetic material is used. It is common practice to use antibiotic prophylaxis in such procedures. Objective: To find out if there is any need of antibiotic prophylaxis in cases of elective open groin hernia repair with prosthetic mesh irrespective of any risk. Methods: Medical record of 145 patients was reviewed retrospectively from January 2017 to January 2019. The information of age, gender, weight, presence of Diabetes mellitus, type of hernia, duration of stay in the hospital, and SSI and its types was recorded in a questionnaire. This data was analyzed to find the correlation between the risk factor and the SSI. Results: SSI was found in 2.8%(n=4) patients (superficial = 3, deep = 1). The mean age of the patients was 48.12 ± 17.27. All the patients were male. 2 patients were diabetic who did not develop SSI. 2.1% (n=3) patients had recurrent inguinal hernia and none of them developed SSI after surgery. The age, gender, weight, Diabetes mellitus, type of hernia, and postoperative stay in the hospital had no significant correlation with the development of SSI. Conclusion: There is no need to administer antibiotic prophylaxis in elective open groin hernia repair with prosthetic mesh in any patient irrespective of the risk.